Investigation of indium nitride for micro–nanotechnology. (8th October 2012) - Gokarna, A.; Lampin, J.F.; Vignaud, D.; Dogheche, E.; Decoster, D.; Ruffenach, S.; Briot, O.; Moret, M.
We present a study of non–intentionally doped InN epilayers directly grown on sapphire substrate by metal organic chemical vapour deposition (MOCVD) technique. Structural and optical characterisations of this sample have been conducted by SEM, temperature–dependent photoluminescence and time resolved pump–probe techniques. Triangular–shaped structures of InN are observed to grow above hexagonal–shaped columnar structures as seen from the SEM image. Photoluminescence spectra reveal a peak energy of 0.75 eV, supporting the existence of the narrow bandgap of InN. So far, various papers in the literature quote the carrier lifetime in InN epilayers grown on sapphire substrate in the presence of a buffer layer such as GaN. Herein, we report carrier lifetime measurements conducted on InN epilayer deposited directly on sapphire substrate, in the absence of GaN as a buffer layer.